THE The Importance of Employee Engagement in Mediating the Improvement of Staff Performance at the Hospital - Nadia Shabrina Amalia; Ratna Indrawati; Endang Ruswanti (Alta Dharma Publisher, 2021)
Staff performance is the success in carrying out the task and achieving the stated goals. Performance can be declared excellent and successful if the desired goals can be appropriately performed. A performance appraisal system is a process that measures employee performance. Several factors affect staff performance, including work motivation, work environment, and employee engagement. The research objective is to analyze the effect of work motivation and physical work environment on staff performance mediated by employee engagement. The type of research was a correlational quantitative analytic study with a cross-sectional research design. The sample population of this study amounted to 92 respondents. The sampling technique used non-random sampling, namely total sampling. The measurement in this study used primary data in the form of a questionnaire distributed to 92 respondents and a questionnaire that returned 84 questionnaires. In this study, the analysis used path analysis. The results showed that work motivation, physical work environment, and employee engagement simultaneously positively and significantly affect staff performance. Partially, work motivation and physical work environment have a positive and significant effect on staff performance. In this study, it was found that employee engagement could mediate an increase in staff performance. Employee engagement and physical work environment have a more significant influence on staff performance than work motivation